Active and Creative Learning Models in Islamic Religious Education: An Analysis of PAKEM and PJBL - Ririn Ristiani; Sri Murhayati; Syuhada Irmadanti (JEICI - Journal of Education and Islamic Contemporary Issue, 2026)
This study aims to analyze active and creative learning models in PAI, particularly through the PAKEM (Active, Creative, Effective, and Fun Learning) and Project-Based Learning (PjBL) approaches. Using a qualitative research method grounded in a literature review, data were obtained from scientific articles and other relevant studies that examined the implementation of the two models. The study's results indicate that active and creative learning models can increase students' motivation, engagement, and creativity in understanding Islamic values. Factors supporting implementation include teacher professionalism, availability of facilities, student motivation, and school support, whereas obstacles include limited time, limited facilities, and resistance to new methods. Overall, PAKEM and PjBL have demonstrated a positive impact on students' mastery of material, character development, and 21st-century skills. Therefore, the development of active and creative learning designs in PAI is essential to addressing educational needs in the digital era and independent curricula.